The Effectiveness of Experiential Marketing Event "HermesFit Indonesia 2023" on Purchase Intention of Hermes Products - Sultan Hasan; Widya Natassha Rachim (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
In recent years, there has been a noticeable increase in the consumption of luxury fashion brands. Consuming and purchasing luxury fashion brands can evoke a sense of pride, exclusivity, and prestige for those who wear them (Chada & Husband 2006). Hermès is a French luxury goods manufacturer since 1837. When viewed in terms of exclusivity, the brand is consistently ranked as the most valuable luxury brand in the world in various assessments and ranking studies published by leading consultants (Leonard, 2021). On September 15 – 17, 2023, Hermès held an event called HermèsFit, which was held at City Hall Pondok Indah Mall 3. This event was created to introduce its new collection to visitors. On the one hand, Hermès also gave visitors experience in using products from their brands. This research aims to measure the level of effectiveness of experiential marketing carried out by the Hermès brand in creating the HermèsFit 2023 event at PIM 3. The theory used in this research is the Elaboration Likelihood Model (ELM) using quantitative method. The research utilized a purposive sampling method with a sample size of 96 respondents whose criteria were JABODETABEK residents who attended the HermèsFit Indonesia 2023 event. This research has an influence between X variable (Experiential Marketing) on Y variable (Purchase Intention) with a regression equation of Y = 1.313 + 0.507 have an influence on Purchase Intention.